The Effect of Cane Material on Length Perception with Long Canes by Visually Impaired, Sighted-Blindfolded, and Sighted Participants. (September 2018) - Penha, Márcio Rogério; Garcia, Ricardo Basso; Vretos, Christina; da Silva, José Aparecido
Introduction: Individuals with visual impairments may use long canes for estimating distances and detecting gaps, obstacles, and texture patterns. The study presented here investigated whether length perception with canes is influenced by cane material. Methods: Visually impaired, sighted-blindfolded, and sighted individuals (n = 30 for each group) participated in this study. Each group was divided into three subgroups (with 5 females and 5 males each) according to cane material. The canes (length = 80 cm, diameter = 1.5 cm) were made of wood, polyethene plastic, or aluminum. The participants were required to judge whether comparison stimuli were shorter than, equal to, or longer than the standard stimulus. Two sessions (for horizontal or vertical lines) were carried out on consecutive days. Results: Cane material was not a significant factor influencing accuracy, F(2, 79) = 2.47, p = .091, and difference threshold, F(2, 79) = 2.01, p = .14, in length perception for the three groups of participants, but cane material interacted with orientation of stimuli, F(2, 79) = 3.24, p = .044. There were significant group differences for accuracy, F(2, 79) = 9.6, p <.001, and difference threshold, F(2, 79) = 8.8, p < .001, revealing that participants with visual impairments were better at discriminating length than sighted-blindfolded participants. Discussion: Our results provide evidence that length perception with canes is not significantly influenced by cane material. The significant group differences for accuracy and difference threshold indicate that assessing visually impaired participants may be more adequate in studies aimed at investigating aspects related to long canes. Implications for practitioners: Orientation and mobility (O&M) instructors can report that there is experimental evidence that cane material is not a significant factor in conveying spatial (length) information, although some evidence suggests that it is a significant factor in conveying tactile information such as the roughness of surface textures.